Bridge knowledge gaps in environmental health and safety for sustainable development of nano-industries. (December 2018) - Liu, Sijin; Lu, Yonglong; Chen, Wei
Graphical abstract: Highlights: Environmental health and safety of ENMs under realistic exposure. Appropriate assays and representative biomarkers for risk assessment. Social acceptability of nano-industry development. Productive green transformation policies for nano-industries. Abstract: Sustainable development of nanotechnology relies on the design and production of engineered nanomaterials (ENMs) with substantial benefits and manageable risks to the environment and human beings, and requires a thorough understanding of environmental health and safety (EHS) impacts. In this review, we elaborate the importance of improved understanding of EHS of ENMs for the sustainable development of nano-industries. Based on our analysis of the current knowledge gaps and challenges in nano-EHS research, we propose that future research directions should mainly focus on: elucidating the impacts of environmental exposure, transport, transformation and fate of EMMs on their toxicity and health risks; identifying more appropriate assays and biomarkers for ENMs risk assessment framework; taking a systems innovation approach for scaling up from laboratory to industrial level.